PID-Based Motion Control of a Differential Drive Robot: A Simulation Study in CoppeliaSim - Setiawan, Fachruddin Ari; Marzani, Ghali; Budianto, Daffa Arkana Sheva; Hadinata, Muhamad Julian (Indonesian Journal of Engineering and Technology (INAJET), 2026)
Motion control is a critical aspect of mobile robot operation, particularly for differential drive robots that require precise regulation of linear and angular velocities. This paper presents the implementation of a PID-based motion control system for a differential drive mobile robot in a CoppeliaSim simulation environment. The proposed control architecture employs two independent PID controllers operating in a closed-loop configuration to regulate the robot’s linear (surge) and angular (yaw) velocities. The robot kinematic model is used to transform the controller outputs into wheel velocity commands. Several simulation scenarios with varying velocity references were conducted to evaluate the performance of the proposed approach. Controller performance was assessed using standard metrics, including transient response characteristics and Root Mean Square Error (RMSE). The simulation results demonstrate that the PID controller achieves stable tracking of the desired velocity references with low tracking errors. The obtained RMSE values of 0.01339 for linear velocity and 0.01496 for angular velocity indicate reliable motion control performance in the simulated environment. The controller performance is further characterized by its steady-state accuracy and transient response behavior during setpoint changes. These findings confirm that PID-based control remains an effective and practical solution for low-level motion control of differential drive robots and provides a solid baseline for further research and experimental validation.